1981
DOI: 10.1111/j.1365-2141.1981.tb02743.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐linked Difference in Blood‐group Distribution Among Patients Suffering From Acute Leukaemias

Abstract: Large numbers of papers have been published on the relationship of different diseases and human blood-groups. Comparing blood-group distribution of a great number of patients suffering from acute leukaemia (AL) to that of control persons, no significant differences could be detected (Shirley & Desai, 1965; Vogel & Helmbold, 1972; Harris et al, 1977).We found blood-group 0 frequency surprisingly high among female patients with AL treated in our clinic between 1974 and 1980. Therefore blood-group distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
2
8
1
Order By: Relevance
“…If our findings can be confirmed, they are compatible with the presence of a gene linked to the ABO genes on chromosome 9 which modifies the risk of AL. It may not be the ABO group itself that protects females from leukemia, because it seems that in different populations the actual ABO group with which this modifying gene is linked varies: in the only other study of this type, a Hungarian group obtained a result opposite to ours (fewer males than females with group O) [8]. Our population here is overwhelmingly Malay, whereas their population would presumably have been mainly white Caucasian.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…If our findings can be confirmed, they are compatible with the presence of a gene linked to the ABO genes on chromosome 9 which modifies the risk of AL. It may not be the ABO group itself that protects females from leukemia, because it seems that in different populations the actual ABO group with which this modifying gene is linked varies: in the only other study of this type, a Hungarian group obtained a result opposite to ours (fewer males than females with group O) [8]. Our population here is overwhelmingly Malay, whereas their population would presumably have been mainly white Caucasian.…”
Section: Discussioncontrasting
confidence: 61%
“…A number of wellknown constitutional syndromes, such as Down and Bloom syndromes, also predispose to acute leukemia. ABO blood groups have been associated with altered risk for a number of malignancies [9,12], but previous studies have found no association of ABO blood group with acute leukemia [7,8]. This hospital treats virtually all the diagnosed cases of AL in northeastern peninsular Malaysia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased proportion of O blood group in female patients with acute leukemia was reported in two previous studies [11,12]. On the other hand, Jackson and colleagues obtained the reverse result in their recent study [10].…”
Section: Discussionmentioning
confidence: 49%
“…Various studies have reported conflicting results about the distribution of blood groups among patients with acute leukemia [8,[9][10][11][12][13][14]. Therefore, we opted to determine the distribution of ABO blood groups among a large number of children with ALL and AML in a multicenter study and compare it with that in normal subjects.…”
mentioning
confidence: 98%